PENGEMBANGAN E-LKPD BERBASIS PROJECT BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA SEKOLAH DASAR - Salamah Tri Rahayu; Ovita, Dhea; Zahra, Amelia; Pramudiyanti, Pramudiyanti; Rohman, Fatkhur (Cerdas Proklamator, 2024)
This study aims to develop E-LKPD teaching materials based on project-based learning by utilizing Thunkable as a learning media for science material on metamorphosis, with a focus on improving critical thinking skills among third-grade elementary school students. This research is a type of development research (Research and Development). The research process includes data collection through validity sheets and practicality sheets in the form of questionnaires containing feedback from teachers and students. The validation team consists of three experts: a subject matter expert, a language expert, and a media expert. The validation results indicate that the feasibility of the E-LKPD is in the very good category, with scores of 96.0% from the media expert, 89.0% from the language expert, and 90.0% from the science subject expert. Student responses to the use of E-LKPD reached 91.5%, while teacher responses reached 96%, both of which fall into the very suitable category. The average effectiveness of using E-LKPD is 89.6%, indicating that the product meets the expected criteria. The results of this study prove that the project-based learning-based E-LKPD is feasible to use in learning and effective in enhancing the critical thinking skills of third-grade elementary school students.